Impact of Cash Flow and Dividend Policy on Manufacturing Firm Value - Ansir Launtu (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
A cash flow statement is a report showing how running, spending, and funding activities impact cash over an accounting period. In addition to cash flow, the dividend policy determines whether the company's earnings will be paid as dividends to investors or retained for reserve funds to support future investments. Firm value is the price a prospective buyer willing to pay if the business is sold. The research objective was to evaluate the impact of cash flow and dividend policies on firm value in Indonesian-listed manufacturing companies (BEI). The research tool used is multiple regression analysis techniques to evaluate the linear relationship between two or more independent variables and the dependent variable. The results showed a small effect of cash flow and dividend policies on firm valuation. Meanwhile, cash flow and dividend strategies have a strong and important effect on firm valuation